REGIONALIZATION SEASONAL AND MONTHLY RAINFALL MAXIMUM RAIN IN THE STATE OF RIO GRANDE DO SUL - Fabiane Pereira Britto; Rodrigo Barletta; Magaly Mendonça (Revista Brasileira de Climatologia, 2008)
This work aims to characterize the rainfall and to identify atmospheric systemsthat act in the Rio Grande do Sul State. Monthly data from the period between1967 and 1998 were used, sampled at the 14 meteorological stations. The timespacialrainfall behavior were analised by the seasonal and monthly variability.Total mean values were calculated for each meteorological stations. Further,data analisys and interpretation were realized on the rainfall (seasonal andmonthly). Seasonal, data for the costal and central state, show that wintermonths are more rainny, due to the frequency of the frontal systems passage.At the southwest, auttumn is more rainny, due to atmospherical blocking. At the northwest, spring months are more rainny, due to Mesoscale ConvectiveComplex formation. At the northeast, summer is more rainny, is a function ofconvective rain associated to atmospheric system like the South AtlanticConvergence Zone.